Transforming Arid and Semi-Arid Areas to be Food Secure: The Role of Small-Scale Irrigation Projects - Kimwaki, Benedict Mutinda (Integrasi Sains Media, 2024)
The primary aim of this research was to evaluate the contribution of irrigation-based initiatives towards ensuring food security. The specific objectives encompassed assessing the role of labor within small-holder irrigation projects in bolstering food security, analyzing the impact of external donor assistance on food security outcomes within these projects, and appraising the extent of governmental backing for small-holder irrigation endeavors in the pursuit of food security goals. Employing a descriptive survey methodology, the study was conducted within various small-holder irrigation projects. The research population consisted of 1303 members affiliated with the irrigation schemes, alongside 12 agricultural officers. Utilizing a simple random sampling technique, two agricultural extension officers were selected from the irrigation schemes, while a stratified sampling approach identified 66 irrigation scheme members for participation in the study. Data collection primarily relied on the administration of questionnaires. Findings revealed that the majority of farmers predominantly relied on their labor or that of family members, with minimal utilization of hired labor observed in small-scale irrigation ventures. Consequently, labor scarcity emerged as a notable challenge within these projects. Furthermore, the study highlighted that a significant proportion of small-holder irrigation initiatives benefited from external donor support. To address labor shortages, the research suggested incentivizing specialized labor while recommending collaborative efforts among farmers to engage specialists in crop management, thereby enhancing crop productivity within the schemes.